Mengevaluasi Pengungkapan ESG Perusahaan: Tingginya Potensi Greenwashing dalam Sustainability Report - Sekar Arum, Lingga; Z. Soeratin, Harry; Miftah, Munasiron (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2024)
This study aims to evaluate the potential for greenwashing in companies' sustainability reports by investigating the internal factors that influence the level of ESG integration in their financial reporting. The research employs a qualitative approach using the literature review method to explore and synthesize findings from various relevant literature sources. The literature search strategy involves combining keywords such as "greenwashing," "sustainability report," "ESG disclosure," and others across prominent academic databases and publications from related organizations. Inclusion criteria include literature discussing greenwashing in the context of sustainability reporting or ESG disclosure, published within the last 10 years. The data analysis utilizes content analysis to identify and categorize key findings related to greenwashing potential, driving factors, and implications for companies and stakeholders. The results highlight the urgency of ESG disclosure, indicators of greenwashing in sustainability reports, the impact of greenwashing on brand reputation, investment attractiveness, and real-world cases such as Coca-Cola's sustainability reporting practices. Additionally, the study examines the implementation of greenwashing in Indonesian companies' sustainability reports, particularly in extractive sectors. The findings provide insights into strategies for enhancing stakeholder trust in corporate environmental practices and building a sustainable future.